Self-management intervention model for optimizing psychological well-being in patients with colorectal stoma - Aryani, Ratna; Lalisang, Toar JM; Dahlia, Debie; Martha, Evi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
A stoma can increase life expectancy and support health recovery but brings several physical and psychosocial issues. Psychosocial resilience is critical in dealing with these changes. This study aims to provide new insights into the interaction between self-management and psychosocial resilience in colorectal cancer stoma patients. This research employs a qualitative design with a case study approach. The study involves colorectal cancer patients with completed primary cancer-related therapies, totaling eight individuals. The informants also include family members of the patients (eight individuals) and volunteer nurses within the community (three individuals). The research instrument is an interview guide structured around five themes. Data analysis follows qualitative stages, encompassing reduction, presentation, and conclusion. Triangulation techniques are utilized to ensure the validity of the findings. The findings suggest that collaboration between family, community, and nurses can provide comprehensive support. However, a structured and focused self-management intervention model is needed to improve psychosocial consistency and resilience. Three models were proposed, namely Family Therapy, Online Community Support, and Nurse Integration in Self-Management, hoping to provide more specific guidance and support for patients. This study provides a basis for developing more varied intervention models and a comprehensive understanding of self-management of colorectal cancer stoma patients.